Development of a technological approach to the control of turbine casings resource for supercritical steam parameters - Chernousenko, Olga; Rindyuk, Dmitro; Peshko, Vitaliy; Goryazhenko, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2018)
A comprehensive model for evaluation of the resource of HPC of the turbine K-800-240-2, which includes calculation of thermal, stressed-strained state, cyclic and static damageability, is presented here. The numerical studies conducted with the use of modern methods of mathematical modeling showed a high impact of forces of pins’ tightening on the stressed-strained state of the casing elements (the stress level increased by 17.7 %). A technological approach to resource control, aimed at a change in pins’ tightening efforts, was proposed. It was established that this method decreases static damageability of basic metal of casings (by 9.7 %), improving its long-term strength. When taking into account tightening forces, the maximum stress intensity decreased by 9.3 %, while the stress level in the flange joint decreased by 11–41 %. These positive moments are accompanied by an increase in individual resource of the casing by 10 %. The developed concept and recommendations have significant importance for ensuring long-term operation of steam turbines with the initial pressure of hot steam at 24 MPa.